If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z+(z-6)-2=-8
We move all terms to the left:
z+(z-6)-2-(-8)=0
We add all the numbers together, and all the variables
z+(z-6)+6=0
We get rid of parentheses
z+z-6+6=0
We add all the numbers together, and all the variables
2z=0
z=0/2
z=0
| 3(a-6)=26 | | 2.1h-5.7-4.6h=1.8 | | x/8=+2=-4 | | -8n=4-9n | | 5p-6p=-7 | | -3=r-4 | | x+(-8)=-5 | | a-2.1=5.8* | | 2g+4=4g | | -(c-7=4 | | Q=(2-4t)/(t+3) | | -2x+12-4=x | | 2(p+7)+11p=0 | | 6=(2x/3)+4 | | x+(-13)=-9 | | 12-3y=2y-17-3y-6 | | 24=7u+u | | 8(u+8)=40 | | 4x+7=-6x+27 | | -4+6s=10s | | 2m-7=5m+14 | | 2(q-9)=8 | | 4x+7=-6x=27 | | 2=m/8 | | 3x+4=0x+2 | | 6(e+4)=30 | | 6z+2z+8=-24 | | y=2(3)^ | | 3x+13=12x+5 | | 9(p-4$=-18 | | -1=m/4 | | 33-3x=31 |